Spectral, Magnetic and Biocidal Studies of Mn(II), Ni(II), Co(II) and Cu(II) Mixed Ligand Complexes - Yadav, B.S.; Sengar, A.K.; Yadav, Rahul (Asian Journal of Chemistry, 2010)
Some bivalent transition metal complexes have been prepared with tinidazole as primary ligand and 4-amino benzoic acid as secondary ligand. The crystalline metal complexes have been characterized by spectral, magnetic studies. The fungicidal behaviour of both ligands with their metal complexes have also been studied against A. niger and A. flavus.